Can We Afford Sustainable Business? - Bertini, Marco; Pineda, John; Petzke, Amadeus; Izaret, Jean-Manuel (MIT Sloan Management Review, 2021)
Companies have struggled with the economics of making sustainable products both affordable and profitable, but that's because they aren't asking the right questions. Rethinking what customers are paying for, who is paying, and how and when the payment occurs can increase access to not only green products but also health care and education. The authors suggest ways businesses can adjust the price mechanism to meet their commitments to improving sustainability and reducing inequity.